Interactive digital TV as revealed through words - focuses and research sources - Buchdid, Samuel B.; Baranauskas, Maria Cecília Calani (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2013)
Interactive Digital TV (iDTV) exists within a digital ecosystem that interconnects a variety of media, viewers and electronic devices, and it reaches new proportions as computers and hyper-connectivity are being incorporated into objects and also into everyday environments, in both public and private spheres. Every emergent technology suffers from a lack of references, processes and artifacts for developers and as they assess and design new solutions. In light of this context, this study sought to map out the main research focuses that have been addressed in the iDTV field in recent years. Data was collected and an analysis was conducted on research sources based on the frequency of words from paper titles and their abstracts; results reveal individual characteristics of one of the most relevant conferences in the field (EuroITV) and other publications found in the ACM-DL. Similarities and differences on these vehicles, allow an overview of contributions and gaps in the field. Moreover, this study presents detailed information about conferences, journals, affiliations and countries where work in the field is registered.